Inovasi Mie Ikan Penja dengan Subtitusi Tepung Kelor dan Tepung Cassava Sebagai Alternatif PMT Balita Gizi Kurang - Syah, Justiyulfah (Nutrition Science and Health Research, 2025)
Undernutrition remains one of the major causes of infant mortality in Indonesia. Providing supplementary feeding (PMT) is one of the key strategies to combat this issue. This study aimed to examine the innovation of penja fish noodles substituted with moringa leaf flour and cassava flour in three formulations: P1 (0:20:80), P2 (3:20:80), and P3 (10:20:80), and to evaluate their acceptability and nutritional content. The research was an empirical laboratory-based study conducted over four months. Organoleptic tests were carried out in Kelurahan Rangas, Majene, and nutritional analysis was performed at the Health Laboratory Center in Makassar. The data were analyzed using a Completely Randomized Design (CRD) and ANOVA. Organoleptic parameters included color, aroma, taste, and texture, while nutritional tests measured fat, protein, carbohydrate, and iron content. The results showed that formula P2 (3:20:80) was the most preferred by consumers and had a balanced nutrient composition. Although some nutrient components did not differ significantly, the substitution improved carbohydrate content. In conclusion, this innovation has the potential to serve as an alternative PMT for undernourished toddlers. Further studies are needed to evaluate its long-term effects and feasibility for broader implementation.